Mathematical Modelling of Chromosome Replication and Replicative Stress - Karschau, Jens (Springer, 2015)
DNA replication is arguably the most crucial process at work in living cells. It is the mechanism by which organisms pass their genetic information from one generation to the next and life on Earth would be unthinkable without it. Despite the discovery of DNA structure in the 1950s, the mechanism of its replication remains rather elusive.